Prevalence and Risk Factors of Acute Pulmonary Embolism in Patients with Lung Cancer Surgery - Li, Yu-ping; Shen, Lei; Huang, Wei; Hu, Xue-fei; Xie, Dong; Yang, Jian; Song, Xiao; Zhao, Yan-feng; Zhou, Chao-jie; Jiang, Ge-ning (Seminars in Thrombosis and Hemostasis, 2018)
Acute pulmonary embolism (PE) is one of the serious complications with high mortality after thoracic surgery. The authors aimed to determine the prevalence of PE events and evaluate additional risk factors for PE in patients with lung cancer surgery. Patients underwent lung cancer resections during January 2012 to July 2015 and had 30-day postoperative follow-up were included. Those with incomplete or miscoded data were excluded. The number of postoperative PE events was recorded retrospectively. Analyses were used to evaluate risk factors of PE during the hospitalization. The authors reviewed 11,474 patients who underwent surgery for lung cancer. The overall 30-day incidence of PE after thoracic surgery at their institution was 0.53%. The 30-day PE incidence without chemical prophylaxis was 0.57% (55/9,726) and the mortality rate was 10%. Multivariate analyses revealed that age over 66 (odds ratio [OR]: 1.09, 95% confidence interval [CI]: 1.05–1.12, p < 0.001), more extensive surgery than lobectomy (OR: 2.34, 95% CI: 1.28–4.25, p = 0.006) and stage IV of lung cancer (OR: 4.22, 95% CI: 1.50–11.9, p = 0.007) were associated with an increased risk of PE. Using these additional risk factors, based on readily available clinical characteristics, can help to risk-stratify patients and warrant extended chemical prophylaxis for patients to reduce the incidence of acute PE.
Keywords: pulmonary embolism; thoracic surgery; lung cancer; chemical prophylaxis; risk factor